2011
DOI: 10.1080/09540121.2010.498873
|View full text |Cite
|
Sign up to set email alerts
|

HIV status disclosure among HIV-positive African and Afro-Caribbean people in the Netherlands

Abstract: HIV status disclosure is often characterized as a dilemma. On the one hand, disclosure can promote health, social support, and psychological well-being. On the other, disclosure can lead to stigmatization, rejection, and other negative social interactions. Previous research has shown that HIV status disclosure is a reasoned process whereby the costs and benefits to oneself and to others are weighed. As such, understanding disclosure requires understanding the reasons for and against disclosure employed by peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 53 publications
7
49
0
1
Order By: Relevance
“…This supports some previous research which has suggested that the quality of the relationship plays a role in disclosure outcomes [e.g. [27][28][29]. This study is the first to draw multiple links between the quality of the relationship and widespread disclosure outcome and it suggests the need for more research in this area.…”
Section: Discussionsupporting
confidence: 73%
“…This supports some previous research which has suggested that the quality of the relationship plays a role in disclosure outcomes [e.g. [27][28][29]. This study is the first to draw multiple links between the quality of the relationship and widespread disclosure outcome and it suggests the need for more research in this area.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies point out that disclosure may also result in stigmatization Valle & Levy, 2009) manifest as, for example, avoidance, rejection, exclusion, blaming, physical distance, and awkward social interaction (Shamos et al, 2009;Stutterheim et al, 2009Stutterheim et al, , 2012. High levels of perceived, anticipated, or internalized stigma, in turn, have been found to yield lower levels of disclosure (Stutterheim, Shiripinda et al, 2011;Tsai et al, 2013;Wolitski et al, 2009). Recent reviews of HIV disclosure research describe a complex and often inconsistent picture of the relationships between disclosure acts, antecedents and outcomes (Chaudoir & Fisher, 2010;Chaudoir et al, 2011;Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption might not hold, as several studies, both qualitative and quantitative, indicate that each act of disclosure to a particular type of actor may have different causes and consequences. For example, disclosure to a partner may be intended to prevent HIV transmission and to gain social support in the context of a steady relationship, disclosing to a family member may aim for emotional or financial support, while disclosing to a broader audience may be motivated by a wish to change the perception of PLWH by the community at large (Greeff et al, 2008;Sowell et al, 2003;Stutterheim, Shiripinda et al, 2011;Vu et al, 2012). Hence, other authors chose to analyze disclosure acts to different actor categories separately (Armistead et al, 1999;Tsai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Especially among Africans, the disclosure of a positive HIV status can be often characterized as a double edged sword where disclosure can either promote or enhance physical, social and psychological wellbeing or result in discrimination, stigmatization, rejection, abandonment, loss of employment, emotional and physical abuse especially directed at women and other negative social consequences [9][10][11]. In spite of this, disclosure remains an integral part of prevention and control within the continuum of the HIV care process.…”
Section: Introductionmentioning
confidence: 99%